Der Club „Gleis 22". 25 Jahre andere Räume, andere Musiken, Kommunikation und Kreativität. - Jacke, Christoph (GLEIS 22 - Fünfundzwanzig Jahre Konzerte.)

Four Subunits ($α$$β$$γ$$δ$) of the Epithelial Sodium Channel (ENaC) Are Expressed in the Human Eye in Various Locations - Krueger, Bettina; Schlötzer-Schrehardt, Ursula; Haerteis, Silke; Zenkel, Matthias; Chankiewitz, Verena E.; Amann, Kerstin U.; Kruse, Friedrich E.; Korbmacher, Christoph (Investigative Opthalmology & Visual Science)
Purpose: The epithelial sodium channel (ENaC) is typically expressed in sodium-absorbing epithelia. Several reports suggest that ENaC is also expressed in ocular tissues and may play a role in aqueous humor secretion and glaucoma. However, the precise localization of ENaC in the human eye is still unclear. Here, the authors studied ENaC expression in 12 normal human donor eyes and in six eyes of patients with glaucoma. Methods: Quantitative real-time PCR was used to investigate the expression of $α$-, $β$-, $γ$-, and $δ$-ENaC transcripts in ocular tissues. In addition, the authors performed immunohistochemical studies using recently generated antibodies against human $β$- and $γ$-ENaC. Results: At the mRNA level, all four ENaC subunits were found to be expressed in a wide range of ocular tissues from normal and glaucomatous human eyes, with the cornea, ciliary body, iris, and retina showing the highest expression levels. At the protein level, $β$- and $γ$-ENaC subunits showed distinct distribution patterns and could be immunolocalized primarily to the cell membranes of epithelial cells of the cornea and to the conjunctiva, iris, ciliary body, lens, and retinal pigment epithelium but also to vascular endothelial cells, smooth muscle cells, stromal cells, and retinal neurons. The authors found no altered mRNA level of any subunit in glaucomatous eyes. Conclusions: All four ENaC subunits ($α$$β$$γ$$δ$) are expressed in the normal human eye, with distinct localization of subunits possibly reflecting different functional states of the channel. The (patho-)physiological roles of ENaC in the various localizations in the eye remain to be determined.

Vectorial secretion of CTGF as a cell-type specific response to LPA and TGF-$β$ in human tubular epithelial cells - Zuehlke, Jonathan; Ebenau, Astrid; Krueger, Bettina; Goppelt-Struebe, Margarete (Cell Communication and Signaling)
Background: Increased expression of the pro-fibrotic protein connective tissue growth factor (CTGF) has been detected in injured kidneys and elevated urinary levels of CTGF are discussed as prognostic marker of chronic kidney disease. There is evidence that epithelial cells lining the renal tubular system contribute to uptake and secretion of CTGF. However, the role of different types of tubular epithelial cells in these processes so far has not been addressed in primary cultures of human cells. Results: Tubular epithelial cells of proximal and distal origin were isolated from human kidneys and cultured as polarized cells in insert wells. The pro-fibrotic stimuli lysophosphatidic acid (LPA) and transforming growth factor $β$ (TGF-$β$) were used to induce CTGF secretion.LPA activated CTGF secretion in proximal tubular cells when applied from either the apical or the basolateral side as shown by immunocytochemistry. CTGF was secreted exclusively to the apical side. Signaling pathways activated by LPA included MAP kinase and Rho kinase signaling. TGF-$β$ applied from either side also stimulated CTGF secretion primarily to the apical side with little basolateral release.Interestingly, TGF-$β$ activation induced different signaling pathways depending on the side of TGF-$β$ application. Smad signaling was almost exclusively activated from the basolateral side most prominently in cells of distal origin. Only part of these cells also synthesized CTGF indicating that Smad activation alone was not sufficient for CTGF induction. MAP kinases were involved in apical TGF-$β$-mediated activation of CTGF synthesis in proximal cells and a subset of epithelial cells of distal origin. This subpopulation of distal tubular cells was also able to internalize recombinant apical CTGF, in addition to proximal cells which were the main cells to take up exogenous CTGF. Conclusions: Analysis of polarized human primary renal epithelial cells in a transwell system shows that vectorial secretion of the pro-fibrotic protein CTGF depends on the cell type, the stimulus and the signaling pathway activated. In all conditions, CTGF was secreted mainly to the apical side upon TGF-$β$ and LPA treatment and therefore, likely contributes to increased urinary CTGF levels in vivo. Moreover, CTGF secreted basolaterally may be active as paracrine pro-fibrotic mediator.

Aldosterone-dependent and -independent regulation of the epithelial sodium channel (ENaC) in mouse distal nephron - Nesterov, Viatcheslav; Dahlmann, Anke; Krueger, Bettina; Bertog, Marko; Loffing, Johannes; Korbmacher, Christoph (American Journal of Physiology-Renal Physiology)
Aldosterone is thought to be the main hormone to stimulate the epithelial sodium channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN) comprising the late distal convoluted tubule (DCT2), the connecting tubule (CNT) and the entire collecting duct (CD). There is immunohistochemical evidence for an axial gradient of ENaC expression along the ASDN with highest expression in the DCT2 and CNT. However, most of our knowledge about renal ENaC function stems from studies in the cortical collecting duct (CCD). Here we investigated ENaC function in the transition zone of DCT2/CNT or CNT/CCD microdissected from mice maintained on different sodium diets to vary plasma aldosterone levels. Single-channel recordings demonstrated amiloride-sensitive Na(+) channels in DCT2/CNT with biophysical properties typical for ENaC previously described in CNT/CCD. In animals maintained on a standard salt diet, the average ENaC-mediated whole cell current ($Δ$I(ami)) was higher in DCT2/CNT than in CNT/CCD. A low salt diet increased $Δ$I(ami) in CNT/CCD but had little effect on $Δ$I(ami) in DCT2/CNT. To investigate whether aldosterone is necessary for ENaC activity in the DCT2/CNT, we used aldosterone synthase knockout (AS(-/-)) mice that lack aldosterone. In CNT/CCD of AS(-/-) mice, $Δ$I(ami) was lower than that in wild-type (WT) animals and was not stimulated by a low salt diet. In contrast, in DCT2/CNT of AS(-/-) mice, $Δ$I(ami) was similar to that in DCT2/CNT of WT animals both on a standard and on a low salt diet. We conclude that ENaC function in the DCT2/CNT is largely independent of aldosterone which is in contrast to its known aldosterone sensitivity in CNT/CCD.

Distinct Mesenchymal Alterations in N-Cadherin and E-Cadherin Positive Primary Renal Epithelial Cells - Keller, Christof; Kroening, Sven; Zuehlke, Jonathan; Kunath, Frank; Krueger, Bettina; Goppelt-Struebe, Margarete (PLOS ONE)
Background: Renal tubular epithelial cells of proximal and distal origin differ markedly in their physiological functions. Therefore, we hypothesized that they also differ in their capacity to undergo epithelial to mesenchymal alterations. Results: We used cultures of freshly isolated primary human tubular cells. To distinguish cells of different tubular origin we took advantage of the fact that human proximal epithelial cells uniquely express N-cadherin instead of E-cadherin as major cell-cell adhesion molecule. To provoke mesenchymal alteration we treated these cocultures with TGF-$β$ for up to 6 days. Within this time period, the morphology of distal tubular cells was barely altered. In contrast to tubular cell lines, E-cadherin was not down-regulated by TGF-$β$, even though TGF-$β$ signal transduction was initiated as demonstrated by nuclear localization of Smad2/3. Analysis of transcription factors and miRNAs possibly involved in E-cadherin regulation revealed high levels of miRNAs of the miR200-family, which may contribute to the stability of E-cadherin expression in human distal tubular epithelial cells. By contrast, proximal tubular epithelial cells altered their phenotype when treated with TGF-$β$. They became elongated and formed three-dimensional structures. Rho-kinases were identified as modulators of TGF-$β$-induced morphological alterations. Non-specific inhibition of Rho-kinases resulted in stabilization of the epithelial phenotype, while partial effects were observed upon downregulation of Rho-kinase isoforms ROCK1 and ROCK2. The distinct reactivity of proximal and distal cells was retained when the cells were cultured as polarized cells. Conclusions: Interference with Rho-kinase signaling provides a target to counteract TGF-$β$-mediated mesenchymal alterations of epithelial cells, particularly in proximal tubular epithelial cells. Furthermore, primary distal tubular cells differed from cell lines by their high phenotypic stability which included constant expression of E-cadherin. Our cell culture system of primary epithelial cells is thus suitable to understand and modulate cellular remodeling processes of distinct tubular cells relevant for human renal disease.

Three-dimensional structure in holographic polymer-dispersed liquid crystals - Redler, Andreas; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Frühe Hilfen sind eine Zukunftsinvestition - Meier-Gräwe, Uta; Wagenknecht, Inga (Frühe Kindheit)

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Energy Flows in Industrial Buildings and Machines using the Example of a Node Model - Schäfer, Mirko; Wagner, Johannes; Schlüter, Alexander; Hesselbach, Jens (SNE Simulation Notes Europe)

A Practical Guide to Polygon Mesh Repairing - Campen, Marcel; Attene, Marco; Kobbelt, Leif (Eurographics 2012 Tutorials)
Digital 3D models are key components in many industrial and scientific sectors. In numerous domains polygonmeshes have become a de facto standard for model representation. In practice meshes often have a number ofdefects and flaws that make them incompatible with quality requirements of specific applications. Hence, repairingsuch defects in order to achieve compatibility is a highly important task - in academic as well as industrial applications. In this tutorial we first systematically analyze typical application contexts together with their requirementsand issues, as well as the various types of defects that typically play a role. Subsequently, we considerexisting techniques to process, repair, and improve the structure, geometry, and topology of imperfect meshes,aiming at making them appropriate to case-by-case requirements. We present seminal works and key algorithms,discuss extensions and improvements, and analyze the respective advantages and disadvantages depending onthe application context. Furthermore, we outline directions where further research is particularly important orpromising.

LIMES - A Time-Efficient Approach for Large-Scale Link Discovery on the Web of Data - Ngonga Ngomo, Axel-Cyrille; Auer, Sören (IJCAI 2011, Proceedings of the 22nd International Joint Conference on Artificial Intelligence, Barcelona, Catalonia, Spain, July 16-22, 2011)

Keyword-Driven SPARQL Query Generation Leveraging Background Knowledge - Shekarpour, Saeedeh; Auer, Sören; Ngonga Ngomo, Axel-Cyrille; Gerber, Daniel; Hellmann, Sebastian; Stadler, Claus (Proceedings of the 2011 {IEEE/WIC/ACM} International Conference on Web Intelligence, WI 2011, Campus Scientifique de la Doua, Lyon, France, August 22-27, 2011)

A Distributed Multi-UAV Path Planning Approach for 3D Environments - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (The 5th International Conference on Automation, Robotics and Applications (ICARA 2011))
During rescue scenarios it is indispensable to obtain an overview of the situation. Unmanned aerial vehicles (UAVs) can gather the necessary information in a fast and efficient way. This paper presents an approach for path planning in 3D environments offering a solution to explore disaster areas including, e.g., partially or completely destroyed buildings. Using multiple UAVs decreases the time needed to receive a complete overview if the problem of coordination and task allocation is solved. We present an approach for the use of multiple UAVs. The UAVs work in a distributed manner without any central coordination instance and cover the exploration of terrains as well as goal-oriented path planning. When using multiple UAVs redundant exploration is avoided through the use of inter-UAV-communication. The approach is based on potential fields and uses the simplicity of the gradient method to calculate paths for fast exploration of the terrain.

Comparison of periodic and aperiodic task models for cyber-physical-systems - Thuy, Andreas (Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC), 2011 6th International Workshop on)

Direction of Associations between Added Sugar Intake in Early Childhood and Body Mass Index at Age 7 Years May Depend on Intake Levels - Herbst, Antje; Diethelm, Katharina; Cheng, Guo; Alexy, Ute; Icks, Andrea; Buyken, Anette (The Journal of Nutrition)

Validation of protein and potassium intakes assessed from 24 h recalls against levels estimated from 24 h urine samples in children and adolescents of Turkish descent living in Germany: results from the EVET! Study - Bokhof, Beate; Buyken, Anette; Doğan, Canan; Karaboğa, Arzu; Kaiser, Josa; Sonntag, Antje; Kroke, Anja (Public Health Nutrition)
Abstract Objective Nutrition-related health problems such as obesity are frequent among children and adolescents of Turkish descent living in Germany, yet data on their dietary habits are scarce. One reason might be the lack of validated assessment tools for this target group. We therefore aimed to validate protein and K intakes from one 24 h recall against levels estimated from one 24 h urine sample in children and adolescents of Turkish descent living in Germany. Design Cross-sectional analyses comprised estimation of mean differences, Pearson correlation coefficients, cross-classifications and Bland–Altman plots to assess the agreement between the nutritional intake estimated from a single 24 h recall and a single 24 h urine sample collected on the previous day. Setting Dortmund, Germany. Subjects Data from forty-three study participants (aged 5–18 years; 26 % overweight) with a traditional Turkish background were included. Results The 24 h recall significantly overestimated mean protein and K intake by 10·7 g/d (95 % CI of mean difference: 0·6, 20·7 g/d) and 344 mg/d (95 % CI 8, 680 mg/d), respectively. Correlations between intake estimates were r = 0·25 ( P = 0·1) and 0·31 ( P = 0·05). Both methods classified 70 % and 69 % of the participants into the same/adjacent quartile of protein and K intake and misclassified 7 % and 7 %, respectively, into the opposite quartile. Bland–Altman plots indicated a wide scattering of differences in both protein and K intake. Conclusions Among children and adolescents of traditional Turkish descent living in Germany, one 24 h recall may only be valid for categorizing subjects into high, medium or low consumers.

Associations between the macronutrient composition of the evening meal and average daily sleep duration in early childhood - Diethelm, Katharina; Remer, Thomas; Jilani, Hannah; Kunz, Clemens; Buyken, Anette (Clinical Nutrition)

Dietary glycaemic index and glycaemic load among Australian children and adolescents - Chun Yu Louie, Jimmy; Buyken, Anette; Heyer, Kristina; Flood, Victoria M. (British Journal of Nutrition)
There are no published data regarding the overall dietary glycaemic index (GI) and glycaemic load (GL) of Australian children and adolescents. We therefore aim to describe the dietary GI and GL of participants of the 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS), and to identify the main foods contributing to their GL. Children, aged 2–16 years, who provided two 24 h recalls in the 2007ANCNPAS were included. A final dataset of 4184 participants was analysed. GI of each food item was assigned using a previously published method. GL was calculated, and food groups contributing to the GL were described by age group and sex. The weighted mean dietary GI and GL of the participants were 54 ( sd 5) and 136 ( sd 44), respectively. Among the nutrients examined, Ca had the highest inverse relationship with GI ( P < 0·001), while percentage energy from starch was most positively associated with GI. The association between fibre density and GI was modest, and percentage energy from sugar had an inverse relationship with GI. Daily dietary GL contributed by energy-dense and/or nutrient-poor (EDNP) items in subjects aged 14–16 years was more than doubled that of subjects aged 2–3 years. To conclude, Australian children and adolescents were having a high-GI dietary pattern characterised by high-starchy food intake and low Ca intake. A significant proportion of their dietary GL was from EDNP foods. Efforts to reduce dietary GI and GL in children and adolescents should focus on energy-dense starchy foods.

Consumption of dietary salt measured by urinary sodium excretion and its association with body weight status in healthy children and adolescents - Libuda, Lars; Kersting, Mathilde; Alexy, Ute (Public Health Nutrition)
Abstract Objective Highly processed foods such as convenience foods usually have a high salt content and therefore might indirectly act as adipogenic due to an increasing consumption of sugar-containing beverages (SCB). We examined the association between dietary salt and body weight status. Design We used data on urinary Na excretion as an indicator of dietary salt and BMI standard deviation score (BMI-SDS) and percentage body fat (%BF) of children and adolescents participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study. Setting Dortmund, Germany. Subjects Children and adolescents ( n 364) who had at least two 24 h urine samples and two dietary records in the observational period between 2003 and 2009 were considered in our data analysis. Results Repeated-measures regression models revealed that urinary Na was positively associated with BMI-SDS (+0·202 SDS/g Na excretion at baseline; P < 0·001) and %BF (+1·303 %BF/g Na excretion at baseline; P < 0·01) at baseline in boys and girls. These associations remained significant after adjustment for SCB consumption and total energy intake. Furthermore, there was a positive trend between baseline Na excretion and the individual change in %BF in the study period (+0·364 increase in %BF/g Na excretion at baseline), which was confirmed after inclusion of SCB consumption or total energy intake. There was no significant association between the change in Na excretion and the concurrent change of either BMI-SDS or %BF in any model. Conclusions Our results suggest that a high intake of processed salty foods could have a negative impact on body weight status in children and adolescents independently from their consumption of SCB.